The Impact of Social Capital on the Attitude-Related Aspects of Strategic Adaptability - Sugiarto, Anton Wachidin Widjaja, (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2020)
This research investigates the impact of social capital which results from social interaction within a horizontal industrial district on the attitude-related aspects of internal and external strategic adaptability. Such foreseen effects are studied from interaction of three dimensions of social capital which occurs indirectly through entrepreneurial behavior and social knowledge exchange. Research data were taken from 450 metal craftsmen in the Tegal municipality and Tegal regency, Central Java, Indonesia. This study reveals that entrepreneurial behavior and social knowledge exchange, which conflicting in nature, have the effects on the internal strategic adaptability, but only entrepreneurial behavior effect the external strategic adaptabilty. The study also reveals that the interaction of two dimensions of social capital have the effects on entrepreneurial behavior and social knowledge exchange due to it was not enough evidence that relational embeddedness act as a social capital which able to strengthen strong ties among entrepreneurs.